Root system markup language: toward an unified root architecture description language - Lobet, Guillaume; Pound, Michael P.; Diener, Julian; Pradal, Christophe; Draye, Xavier; Godin, Christophe; Javaux, Mathieu; Leitner, Daniel; Meunier, Felicien; Nacry, Philippe; Pridmore, Tony P.; Schnepf, Andrea (American Society of Plant Biologists, 2015)
The number of image analysis tools supporting the extraction of architectural features of root systems has increased over the last years. These tools offer a handy set of complementary facilities, yet it is widely accepted that none of these software tool is able to extract in an efficient way growing array of static and dynamic features for different types of images and species.